PENGARUH USAHA BATU BATA TERHADAP PENDAPATAN RUMAH TANGGA DESA SOREK DUA KABUPATEN PELALAWAN - Putri Clawson; Lukman Markus (P3M STKIP 'Aisyiyah Riau, 2015)
The purpose of this study is to determine whether the brick business affects household income in the Village of Sorek Dua, Pangkalan Kuras District, Pelalawan Regency. With the poverty rate showing quite high below the poverty line this year the poverty rate is estimated to be 11.40 percent, this is due to lack of knowledge in utilizing natural resources. Data collection techniques used in this study are by observation, interviews, questionnaires and documentation using the Statistical Product and Service Solution (SPSS) program version 17.0. Based on the results of the study, it was concluded that the average income of each bricklayer family per month was Rp.5,747,692, - and the average expenditure per bricklayer family in one month was Rp.3,263,900. The effect of brick business income on family income has a moderate effect, which is 79%, which means the brick business in Sorek Dua Village is classified as having a very good influence so that the business is feasible to develop and develop.